A Preliminary Study of the Influence of Age of Onset and Childhood Trauma on Cortical Thickness in Major Depressive Disorder. (6th March 2014) - Jaworska, Natalia; MacMaster, Frank P.; Gaxiola, Ismael; Cortese, Filomeno; Goodyear, Bradley; Ramasubbu, Rajamannar
Abstract : Background . Major depressive disorder (MDD) neural underpinnings may differ based on onset age and childhood trauma. We assessed cortical thickness in patients who differed in age of MDD onset and examined trauma history influence. Methods . Adults with MDD (N = 36 ) and controls (HC; N = 18 ) underwent magnetic resonance imaging. Twenty patients had MDD onset < 24 years of age (pediatric onset) and 16 had onset > 25 years of age (adult onset). The MDD group was also subdivided into those with (N = 12 ) and without (N = 19 ) physical and/or sexual abuse as assessed by the Childhood Trauma Questionnaire (CTQ). Cortical thickness was analyzed with FreeSurfer software. Results . Thicker frontal pole and a tendency for thinner transverse temporal cortices existed in MDD. The former was driven by the pediatric onset group and abuse history (independently), particularly in the right frontal pole. Inverse correlations existed between CTQ scores and frontal pole cortex thickness. A similar inverse relation existed with left inferior and right superior parietal cortex thickness. The superior temporal cortex tended to be thinner in pediatric versus adult onset groups with childhood abuse. Conclusions . This preliminary work suggests neural differences between pediatric and adult MDD onset. Trauma history also contributes to cytoarchitectural modulation. Thickened frontal pole cortices as a compensatory mechanism in MDD warrant evaluation.